2017
DOI: 10.1038/s41467-017-01470-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and detection of low-allele-fraction variants in clinical cancer samples

Abstract: Accurate detection of genomic alterations using high-throughput sequencing is an essential component of precision cancer medicine. We characterize the variant allele fractions (VAFs) of somatic single nucleotide variants and indels across 5095 clinical samples profiled using a custom panel, CancerSCAN. Our results demonstrate that a significant fraction of clinically actionable variants have low VAFs, often due to low tumor purity and treatment-induced mutations. The percentages of mutations under 5% VAF acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
181
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 167 publications
(185 citation statements)
references
References 40 publications
3
181
1
Order By: Relevance
“…Targeted massively parallel sequencing was performed using Illumina HiSeq 2,500‐based CancerSCAN designed at Samsung Medical Center and covered 6,839 exons from 381 cancer‐related genes and introns from 23 genes in 380 GC and the list of genes are described in Supporting Information Table S2. The selected genes covered variants associated with targeted cancer therapies approved by the US FDA, genes related to clinical trials at the Precision Oncology Clinic at Samsung Medical Center, and genes reported to have an association with response to therapy in public databases and the literature . High‐quality results (mean depth >200; 99.0% > 100X; >30% on bait; duplication rate <75) were obtained in 330 cases and were further analyzed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Targeted massively parallel sequencing was performed using Illumina HiSeq 2,500‐based CancerSCAN designed at Samsung Medical Center and covered 6,839 exons from 381 cancer‐related genes and introns from 23 genes in 380 GC and the list of genes are described in Supporting Information Table S2. The selected genes covered variants associated with targeted cancer therapies approved by the US FDA, genes related to clinical trials at the Precision Oncology Clinic at Samsung Medical Center, and genes reported to have an association with response to therapy in public databases and the literature . High‐quality results (mean depth >200; 99.0% > 100X; >30% on bait; duplication rate <75) were obtained in 330 cases and were further analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…SNVs and indels were detected by MuTect 1.1.4 and Pindel 0.2.5a4 . For CNV, we used the same criteria as previously described …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To remove common germline polymorphisms, variants were filtered using public and in-house databases. 27 Variants were chosen if they were located in exonic regions, and synonymous variants were filtered out. SNVs with a frequency of 1% with at least five supporting reads were chosen for further analyses.…”
Section: Biomarker Analysismentioning
confidence: 99%